Klinefelter's syndrome (47,XXY) is in excess among men with Sjögren's syndrome (2016)
Primary Sjögren's syndrome (pSS) has a strong female bias. We evaluated an X chromosome dose effect by analyzing 47,XXY (Klinefelter's syndrome, 1 in 500 live male births) among subjects with pSS. 47,XXY was determined by examination of fluorescence intensity of single nucleotide polymorphisms from the X and Y chromosomes. Among 136 pSS men there were 4 with 47,XXY. This was significantly different from healthy controls (1 of 1254 had 47,XXY, p = 0.0012 by Fisher's exact test) as well men with rheumatoid arthritis (0 of 363 with 47,XXY), but not different compared to men with systemic lupus erythematosus (SLE) (4 of 136 versus 8 of 306, Fisher's exact test p = NS). These results are consistent with the hypothesis that the number of X chromosomes is critical for the female bias of pSS, a property that may be shared with SLE but not RA. © 2016.